Developing the OPAN workforce: Exploring the skills, attributes, knowledge, professional development, and training requirements for effective aged care advocacy - Hayden-Evans, Maya; Blundell, Barbara; Milbourn, Ben (2020)
This research project was conducted by Curtin University and commissioned by the Older Persons Advocacy Network (OPAN) to explore professional development opportunities for aged care advocates, as well as the skills, competencies and training required to work effectively in the role.